Reviewing The Legal Status of the Joint Ministerial Decrees in Indonesian State Administrative Law - Suwiryo Prawira; Dion Nupianto (Candela Edutech Indonesia, 2026)
The implementation of state governance based on the concept of a material rule of law requires discretion as an adaptive mechanism to prevent stagnation and legal vacuum. This is manifested in practice in the form of the government's authority (freies ermessen) in making decisions. As is practiced in Indonesia, for example, several government officials or ministers under certain legal circumstances issue a single decision simultaneously called a